1998
DOI: 10.1109/36.673673
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian classification and class area estimation of satellite images using stratification

Abstract: The paper describes an iterative extension to maximum a posteriori (MAP) supervised classification methods. A posteriori probabilities per class are used for classification as well as to obtain class area estimates. From these, an updated set of prior probabilities is calculated and used in the next iteration. The process converges to statistically correct area estimates.The iterative process can be combined effectively with a stratification of the image, which is made on the basis of additional map data. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 9 publications
1
36
0
1
Order By: Relevance
“…Split-and-merge segmentation consists of a region-splitting phase and an agglomerative clustering (merging) phase (Haralick and Shapiro 1985, Horowitz and Pavlidis 1976, Gorte and Stein 1998, Lucieer and Stein 2002, Lucieer et al 2004. Supervised segmentation uses explicit knowledge about the study area to train the segmentation algorithm on reference textures.…”
Section: Texture Based Image Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Split-and-merge segmentation consists of a region-splitting phase and an agglomerative clustering (merging) phase (Haralick and Shapiro 1985, Horowitz and Pavlidis 1976, Gorte and Stein 1998, Lucieer and Stein 2002, Lucieer et al 2004. Supervised segmentation uses explicit knowledge about the study area to train the segmentation algorithm on reference textures.…”
Section: Texture Based Image Segmentationmentioning
confidence: 99%
“…Segmentation techniques extract spatial objects from an image (Gorte andStein 1998, Lucieer andStein 2002). It extends classification, as spatial contiguity is an explicit goal of segmentation whereas it is only implicit in classification.…”
Section: Introductionmentioning
confidence: 99%
“…If the data are complex in structure, then to model the data in an appropriate way can become a real problem. [6] have used Bayesian classification for class area estimation of satellite images using stratification. LAU C.C.…”
Section: Introductionmentioning
confidence: 99%
“…Gorte and Stein (1998) showed that higher overall accuracy can be achieved by localized k -nearest neighbour estimation of the probability density P (x p |C i ).…”
Section: Land Cover Imagery and Air Quality Datamentioning
confidence: 99%
“…In each training region 14 areas were selected representatively in terms of land cover classes and variations in soil types. From each training area, 20-30 pixels were selected resulting in a training sample size that was within the recommended range for maximum likelihood classification (Gorte and Stein, 1998). The training samples were the basis for signature development for the ML classifier and for determining NDVI thresholds for the bare ground, water and vegetation classes.…”
Section: Land Cover Imagery and Air Quality Datamentioning
confidence: 99%